Structural study of plant cellulose synthase and atypical profilin3 - Qiao, Zhu (Nanyang Technological University, 2020)
Plant cellulose synthase (CesA) catalyzes the biosynthesis of cellulose which is the most abundant biomass on earth. CesA belongs to the GT-2 Glycosyltransferase family encoding the canonical signature (D, D, D, QXXRW motif), while its structure remains elusive after its first identification in cotton. I solved the first crystal structure of the Arabidopsis thaliana CesA3 catalytic domain with the apo and UDP-Glucose binding form. The conserved inner core GT domain was surrounded by P-CR and C-SR domains. The UDP-Glucose binding and orientation of the conserved QxxRW motif were quite different from the bacterial BcsA. Moreover, the CesA3 catalytic domain was a homo-dimer in solution and the dimer interfaces were generally formed by “edge to edge” interaction. Disrupting the “edge to edge” interaction transforms the dimer to the monomer state in solution, which was also validated by the in vivo BIFC experiment. A low-resolution model of oligomeric full-length cellulose synthase was also obtained by Cryo-EM. Besides, crystal structures Arabidopsis PRF2 and PRF3 were determined to reveal the dynamics of PRF3 N terminal extension towards to the poly-proline binding.